2020
DOI: 10.3389/frobt.2020.00107
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Regulation Using Plasticoding for the Evolution of Robots

Abstract: Evolutionary robot systems are usually affected by the properties of the environment indirectly through selection. In this paper, we present and investigate a system where the environment also has a direct effect—through regulation. We propose a novel robot encoding method where a genotype encodes multiple possible phenotypes, and the incarnation of a robot depends on the environmental conditions taking place in a determined moment of its life. This means that the morphology, controller, and behavior of a robo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Thirdly, the mechanism of plasticity is not perfect: sometimes robots look almost the same in both seasons (Fig. 7), and as shown previously, robots evolved with this plasticity capacity tend to be less fit than those evolved in each season separately (Miras et al, 2020a). The relation between these three reasons is that perhaps a genetic pool biased to one season would not be a problem if the portions of genetic material that code for the other season were optimally delineated by the mechanism of regulation.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Thirdly, the mechanism of plasticity is not perfect: sometimes robots look almost the same in both seasons (Fig. 7), and as shown previously, robots evolved with this plasticity capacity tend to be less fit than those evolved in each season separately (Miras et al, 2020a). The relation between these three reasons is that perhaps a genetic pool biased to one season would not be a problem if the portions of genetic material that code for the other season were optimally delineated by the mechanism of regulation.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, the genotype encodes regulatory clauses that allow phenotypic plasticity -through these clauses, robots can develop different morphologies and controllers depending on environmental conditions. This particular encoding, decoding, and regulatory design were proposed by (Miras et al, 2020a), where more details about them and their variation operators can be found. In summary, each genotype is a distinct grammar, making use of the same alphabet.…”
Section: Encodingmentioning
confidence: 99%
See 3 more Smart Citations